Analyzing Muhammad ’Abdah’s Approach to Tafsir and Its Impacts - Hafiza Raheela Butt; Dr. Muhammad Akram Choudhary (jihat-ul-islam, 2023)
The article aims at analyzing critically the sources of Shiekh Muhammad Abduhu referred to while writing his tafsir of the Holy Qur’an. Sheikh Abduhu, as a modernist of the twentieth century, challenged the orthodox interpreters of the Holy Qur’an. In this short study we have tried to analyze the impact of his views on the Tafsir Studies particularly on those who followed him. Under the influence of the West, Sheikh adopted the rational and scientific approach toward the Qur’an. Through this study, the researchers will understand that Shiekh Muhammad Abduhu had rejected all the standard principles set by orthodox and established schools of thought pertaining to Tafsir literature and had given preference to his personal ideas. Inspired by his ideas in the post-modern times, many scholars are following him and have pursued his mission.